1985
DOI: 10.1029/ja090ia05p04229
|View full text |Cite
|
Sign up to set email alerts
|

A statistical model of auroral electron precipitation

Abstract: A statistical study has been completed using data from the Defense Meteorological Satellite Program F2 and F4 and the Satellite Test Program P78‐1 satellites to determine the average characteristics of auroral electron precipitation as a function of magnetic local time, magnetic latitude, and geomagnetic activity as measured by Kp. The characteristics were determined for each whole number value of Kp from 0 to 5 and for Kp ≥ 6‐. At each level of Kp, the high‐latitude region was gridded, and the average electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
395
9

Year Published

1992
1992
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 484 publications
(440 citation statements)
references
References 43 publications
34
395
9
Order By: Relevance
“…By restricting our analysis to quiet geomagnetic conditions only, i.e., Kp ≤ 2, Joule heating [Kosch and Nielsen, 1995] and heat flux of ions and electrons due to particle precipitation also become negligible [cf. Hardy et al, 1985Hardy et al, , 1989, allowing us to assume equal ion and neutral temperatures. Quiet geomagnetic conditions permit us to assume a steady state ion motion, so that the time derivative of the ion velocity is also ignored.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…By restricting our analysis to quiet geomagnetic conditions only, i.e., Kp ≤ 2, Joule heating [Kosch and Nielsen, 1995] and heat flux of ions and electrons due to particle precipitation also become negligible [cf. Hardy et al, 1985Hardy et al, , 1989, allowing us to assume equal ion and neutral temperatures. Quiet geomagnetic conditions permit us to assume a steady state ion motion, so that the time derivative of the ion velocity is also ignored.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The precipitating cold (average energy <1 keV) and hot (>1 keV) electrons were defined following Hardy's model requirements (Hardy et al, 1985). The maximum flux intensity of the precipitating cold electrons (with the average electron energy of E 0 =0.27 keV) in the region of the daytime cusp was I m = 1.9 · 10 9 cm −2 s −1 .…”
Section: Model Calculationsmentioning
confidence: 99%
“…These five orbits represent the variability found during this 24-hour period, including one pass during the substonn. Figure 2 shows the selected passes, approximated as straight lines, in the polar magnetic coordinates with a Hardy et al [1985] auroral oval shown as the shaded region. Each DE 2 passage is labeled with the approximate time at which the orbit crossed the dawnside northern high-latitude region.…”
Section: Y-------~------------------------------~mentioning
confidence: 99%
“…At the present time, no globalscale theoretical model of the magnetosphere exists. Hence, statistical (empirical) models of the magnetospheric electric field [Volland, 1978;Heelis et al, 1982;Sojka el al., 1986;Heppner and Maynard, 1987] and auroral precipitation [Spiro et aI., 1982;Hardy et al, 1985;Evans , 1987] are used as inputs to ionospheric and thennospheric models. Such studies are handicapped because statistical inputs cannot readily be adapted to simulate the spatial variations and temporal dynamics of geomagnetic storms and substorms.…”
Section: In'rroducnonmentioning
confidence: 99%